(untitled) (Patan Pragya, 2025)
The TU’s MA Sociology academe has completed with the highest international sociological curricula by maintaining its strong motivation. Now, to analyze the strengths and weaknesses of the MA Sociology Curriculum (2025) at Tribhuvan University based on international standards. In this contest, the paper-wise assessment requires to reflect theoretical, methodological, and issue-wise wisdom, investigation orientation, significance, and international malleability. The objectives are to analyze the Sociology, and some compare them with other universities. The Curriculum Analysis of the master’s Level Sociology Program in Tribhuvan University and compares the Curriculum of the Program in other Universities. The method had applied to study has a Review of the previous and current curriculum, compared with global ’ courses of study of master level. The comparison with some other different reasons and continents has operating practices, like North America, Europe, and South Asian universities. Nepalese first and Millstone University TU provides the best theoretical foundation and provide sound research approaches in new emerging issues, but some weak emphasis on modern techniques like vast data analytics, which are gradually essential to global sociology. The differences in the curriculum are less adaptive to digital changes, misplaced areas like algorithmic bias, digital characters, and virtual governance, and it also engages a good teaching method, but imperfect connection with resources, international partnerships, and interdisciplinary methods, which are important in the best collective plans. Analytical method has been applied for acquiring the objectives. The major Strengths of TU’s Program are a Strong theoretical foundation in traditional and modern sociological models. It is necessary to place Importance on the Nepali and South Asian situation, creation it applicable for local scholars and as well as Applied research emphasis through thesis writing and field-based projects.